2011
DOI: 10.1155/2011/614546
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Brucellosis Presenting with Multiple Hypodense Splenic Lesions and Bilateral Pleural Effusions

Abstract: Brucellosis is a zoonotic infectious disease, which mainly present with lymphoreticular system invovement. However any organ system can be attacked by the microorganism. In this paper we present a 52-year-old female patient who was admitted to the Infectious Diseases Department with complaints of fatigue, arthralgias, fever, and weight loss. In the medical examination and radiological analysis bilateral pleural effusions and hepatosplenomegaly were detected. Serum transaminase levels were two times higher than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Pulmonary involvement secondary to bacteraemia has also been seen in brucellosis and can rarely manifest as empyema, pleural effusions, pulmonary nodules and mediastinal lymphadenopathy 8. Although our patient had a single episode of unwitnessed haemoptysis, there was no evidence of pulmonary involvement on the chest radiography or CT scan.…”
Section: Discussionmentioning
confidence: 52%
“…Pulmonary involvement secondary to bacteraemia has also been seen in brucellosis and can rarely manifest as empyema, pleural effusions, pulmonary nodules and mediastinal lymphadenopathy 8. Although our patient had a single episode of unwitnessed haemoptysis, there was no evidence of pulmonary involvement on the chest radiography or CT scan.…”
Section: Discussionmentioning
confidence: 52%
“…Two similar findings had also been reported by others. [19,20] Solitary abscess had calcification, but multiple smaller abscesses showed few calcifications. [18] Our study reported CT examination showed no calcification with multiple smaller abscesses in the spleen or liver.…”
Section: Discussionmentioning
confidence: 99%
“…These focal forms may include osteoarticular, neurological, genitourinary, liver, hematological, and cardiac involvements [ 2 ]. Brucella bacteremia can also cause abscess formation in the spleen, liver, or other organs [ 5 ]. Nevertheless, some forms of focal involvement such as hepatosplenic abscesses and multifocal or extraspinal osteomyelitis have rarely been seen and they are quite uncommon.…”
Section: Discussionmentioning
confidence: 99%
“…Our report also described a rare presentation of acute brucellosis with bacteremia and multiple hepatosplenic lesions. Although hepatomegaly and splenomegaly are frequent findings on physical examination, a more unusual complication of human brucellosis is the development of abscesses of the liver and spleen [ 5 ]. In a study by Colmenero et al hepatosplenic abscesses were detected in 0.8% of 805 patients [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation